The Analysis of Counselor Personal Competence in the Era of Industry 4.0 in South Sulawesi - Abdul Saman; Muhammad Arifin Ahmad; Muhammad Ilham Bakhtiar (Journal of Educational Science and Technology (EST), 2020)
The aims of the study are (1) to explore the influence of years of service on the counselor personal competence in the Era of Industry 4.0 in South Sulawesi; (2) to investigate the influence of counselor age on their personal competence in the Era of Industry 4.0 in South Sulawesi; and (3) to explore the influence of education level on the counselor personal competence in the Era of Industry 4.0 in South Sulawesi. The study employed a survey method using a questionnaire and data were analyzed descriptively with Anova and Multivariate. The validity and reliability of the questionnaire and the homogeneity of variables were priorly tested. The study involved 215 teachers from Junior High School, Senior High School, and Vocational High School in South Sulawesi. The findings indicate that the years of service influences the counselor's personal competence in the Era of Industry 4.0. Based on the Test of Between-Subjects Effect analysis, the longer they work, the better their personal competence in providing guidance and counseling services. Results of post hoc Test Multiple Comparisons analysis between years of service and personal competence and competence of era 4.0 shows that productive service years results in good personal competence in implementing the service from the 2nd  to the 20th years., and the ideal workers in the era of industry 4.0 is the new counselor. (2) Educational level influences the Counselor Personal Competence in the Era of Industry 4.0 according to the Test of Between-Subjects Effect. Thus, it is clear that the higher the educational level of the counselor, the better they are in providing guidance and counseling to students; (3) the age of Guidance and Counseling Teachers/ Counselor influences their personal competence in era 4.0. Based on the Test of Between-Subjects Effect, teachers’ ages are highly influential to increase the service in the era 4.0.berarti which means that it is directly proportional to the years of service. In this case, the more years the counselor works, and the older they are, the better they provide guidance and counseling service.